# kx^2+4x+(5-k)=0

## Simple and best practice solution for kx^2+4x+(5-k)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for kx^2+4x+(5-k)=0 equation:

Simplifying
kx2 + 4x + (5 + -1k) = 0

Remove parenthesis around (5 + -1k)
kx2 + 4x + 5 + -1k = 0

Reorder the terms:
5 + -1k + kx2 + 4x = 0

Solving
5 + -1k + kx2 + 4x = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -1k + kx2 + -5 + 4x = 0 + -5

Reorder the terms:
5 + -5 + -1k + kx2 + 4x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -1k + kx2 + 4x = 0 + -5
-1k + kx2 + 4x = 0 + -5

Combine like terms: 0 + -5 = -5
-1k + kx2 + 4x = -5

Add '-4x' to each side of the equation.
-1k + kx2 + 4x + -4x = -5 + -4x

Combine like terms: 4x + -4x = 0
-1k + kx2 + 0 = -5 + -4x
-1k + kx2 = -5 + -4x

Reorder the terms:
5 + -1k + kx2 + 4x = -5 + -4x + 5 + 4x

Reorder the terms:
5 + -1k + kx2 + 4x = -5 + 5 + -4x + 4x

Combine like terms: -5 + 5 = 0
5 + -1k + kx2 + 4x = 0 + -4x + 4x
5 + -1k + kx2 + 4x = -4x + 4x

Combine like terms: -4x + 4x = 0
5 + -1k + kx2 + 4x = 0

The solution to this equation could not be determined.`